Electrochemical Investigation on Adsorption of Fluconazole at Mild Steel/HCl Acid Interface as Corrosion Inhibitor. (30th December 2012) - Jebakumar Immanuel Edison, T.; Sethuraman, M. G.
Abstract : The interfacial behavior of fluconazole on mild steel in 1 M HCl solution was studied by electrochemical methods, namely, polarization (Tafel Plot) and Electrochemical Impedance Spectroscopy (EIS). The surface morphology of mild steel in the presence and absence of fluconazole was studied by Atomic Force Microscopy (AFM). The results of the study showed that fluconazole reduced the corrosion rate in HCl acid solution by adsorbing on the surface of mild steel. Tafel results suggest that fluconazole behaves predominantly as an anodic inhibitor and shows greater inhibition efficiency (96%) at 0.30 mM. Thermodynamical parameters suggest that fluconazole is adsorbed on mild steel mainly by chemical mode. The EIS studies reveal the formation of a thin barrier film on mild steel surface. The AFM image of mild steel immersed in optimum concentration of fluconazole has confirmed the film formation on metal surface.